The determinants of saccade targeting strategy in neurodevelopmental disorders: The influence of suboptimal reading experience. (March 2023) - Vernet, Marie; Bellocchi, Stéphanie; Danna, Jérémy; Massendari, Delphine; Jover, Marianne; Chaix, Yves; Ducrot, Stéphanie
Abstract: Whether eye-movements deficits are causal in reading disorders (RD) or rather a consequence of linguistic processing difficulty experienced by disabled readers has been extensively debated. Since RD are frequently comorbid with the Neurofibromatosis type1 (NF1), children with NF1 were used as a comparison group for children with dyslexia in this study. Eye movements were recorded while 21 dyslexic, 20 NF1, and 20 typically developing children performed an oculomotor lateralized bisection task. In this experiment, we manipulated the type of stimulus - discrete (words and strings of hashes) versus continuous (solid lines) - and the visual field where the stimulus was displayed (left vs right). The results showed that (1) only proficient readers (TD and NF1 without RD) showed fully developed oculomotor mechanisms for efficient reading, with a clear preferred viewing location located to the left of the word's centre in both visual fields, and fine-tuned saccade targeting guided by the between-character space information and (2) NF1 poor readers mirrored the dyslexic eye movement behaviour, with less accuracy and more variability in saccadic programming, no sensitivity to the discreteness of the stimuli, particularly in the left visual field. We concluded that disruption to oculomotor behaviour reflects the fact that many of the processes involved in reading are not yet automatized for children with RD, independently of NF1. This suggests that the differences in saccade targeting strategy between children with and without RD would be secondary consequences of their reduced reading experience.